Modeling demyelination and endogenous remyelination in spinal cord ex vivo rat organotypic slice cultures - Hawker, Brooke; Dhakal, Muna; Connor, Bronwen; McCaughey-Chapman, Amy (Frontiers in Cellular Neuroscience, 2024)
Demyelination of the spinal cord is a prominent feature of multiple sclerosis (MS) and spinal cord injuries (SCI), where impaired neuronal communication between the brain and periphery has devastating consequences on neurological function. Demyelination precedes remyelination, an endogenous process in which oligodendrocyte precursor cells (OPCs) differentiate into mature, myelinating oligodendrocytes with the ability to restore the myelin sheath and reinstate functional nerve signalling. However, in MS or SCI, demyelination is more severe, persistent, and inhibitory to OPC-mediated remyelination, leading to a permanent loss of neuronal function. Currently, there are no effective treatments for demyelination, and existing pre-clinical models typically focus on brain tissue with little characterisation of demyelination within the spinal cord. Organotypic slice cultures are a useful tool to study neurological disease, providing a more complex 3-dimensional system than standard 2dimensional in vitro cell cultures. Building on our previously developed rat brain slice culture protocol, we have extended our findings to develop a rat longitudinal spinal cord ex vivo model of demyelination. We generated rat longitudinal spinal cord slice cultures that remain viable for up to 6 weeks in culture and retain key anatomical features of the spinal cord's cytoarchitecture. We show that treating longitudinal spinal cord slices with lysolecithin (LPC) induced robust demyelination with some endogenous remyelination, which was not seen following exposure to lipopolysaccharide (LPS). Our ex vivo organotypic spinal cord slice culture system provides a platform to model demyelination and endogenous remyelination long-term, mimicking that observed in LPC-induced rodent models of demyelination. This platform is suitable for the development and testing of novel therapeutic strategies with ease of manipulation prior to in vivo experimentation.